Аналіз біометричних методів автентифікації в інфокомунікаційних мережах - Лавренчук, А. А.; Пастушенко, М. С. (ХНУРЕ, 2025)
Biometric authentication methods play a crucial role in ensuring security in modern infocommunication networks. Traditional authentication methods, such as passwords and tokens, present significant vulnerabilities, including theft, forgery, and management complexity. Biometric systems leverage unique physiological and behavioral characteristics for user identification, offering higher reliability and ease of use. The paper highlights innovative biometric authentication methods, including neuroauthentication via EEG signals, dynamic biometrics based on eye micro movements and gait analysis, and countermeasures against deepfake-based threats. It also explores blockchain-based biometric template protection and quantum-resistant cryptography as future-proofing measures.
Keywords: метод автентифікації; biometric authentication method